IL-33 contributes to disease severity in Psoriasis-like models of mouse. (July 2019) - Duan, Yaju; Dong, Yonghua; Hu, Hua; Wang, Qiumei; Guo, Sheng; Fu, Dandan; Song, Xiangfeng; Kalvakolanu, Dhan V.; Tian, Zhongwei
Abstract: Immune cells infiltrating the psoriatic skin secrete high amounts of pro-inflammatory cytokines IL-17, TNF-α, IL-21 and IL-36 resulting in chronic inflammation. However, the exact cellular and molecular mechanisms have not been fully understood. We report here elevation of IL-33 expression in psoriatic lesions. Studies in imiquimod (IMQ)-induced mice with psoriatic inflammation confirmed a critical role for IL-33 in driving the disease. IL-33 reduces the CD4 + and CD8 + cells, inhibits autophagy in IMQ-treated mouse skin, and promoted tyrosyl phosphorylation of STAT3. Thus, IL-33 appears to be a major risk factor for severity of psoriasis-like skin inflammation. Our findings may open new perspectives for understanding the mechanisms and developing a therapeutic strategy for psoriasis.